The Pertumbuhan dan produktivitas kacang merah (Phaseolus vulgaris L.) setelah pemberian eco enzyme limbah tebu pada tanah gambut - Rizqi, Laely; Zakiah, Zulfa; Ifadatin, Siti (Jurnal Biologi Udayana; Vol 27 No 2 (2023): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2023.v27.i02.p09, 2024)
Red bean (Phaseolus vulgaris L.) is a vegetable commodity in West Kalimantan Province which has a low production compared to other vegetable commodities. Several attempts were made to increase the production of red beans (Phaseolus vulgaris L.), one of which is by applying liquid organic fertilizer. Organic materials such as sugar cane waste are often found in Pontianak City, and it can be used to make eco enzyme which can be used as organic fertilizer for red bean plants (Phaseolus vulgaris L.). The purpose of this study was to determine the effect of sugarcane waste eco enzyme administration on the growth and production of kidney beans (Phaseolus vulgaris L.). This study used a completely randomized design (CRD) with 7 treatment levels, namely Greentonic LOF (positive control), 0 mL/L  eco enzyme (negative control), 0.5 mL/L  eco enzyme (A1), 1 mL/L  eco enzyme (A2), 1.5 mL/L  eco enzyme (A3), 2 mL/L  eco enzyme (A4) and 2.5 mL/L  eco enzyme (A5). The results showed that the administration of eco enzymes from sugarcane waste had a significant effect on plant height, chlorophyll content, fresh weight and dry weight of red bean (Phaseolus vulgaris L.) seeds. Giving eco enzyme with a concentration of 2.5 mL/L  gave the best results for the growth parameters of plant height 53 cm and chlorophyll content 3.19 mg/L. While giving eco enzyme with a concentration of 1 mL/L  gave the best results for production parameters of seed wet weight 3.64 g and seed dry weight 0.80 g.